Association of relative deprivation with loneliness and its underlying mechanisms: Evidence from Chinese migrant children - Xiong, Meng; Xu, Wenxi (Frontiers in Psychology, 2023)
Given the increase in the number of internal migrant children, the mental health problems (e.g., loneliness) of this population have received widespread attention. Relative deprivation is considered to be related to migrant children’s loneliness. However, the underlying mechanisms of this relationship remain unclear. Therefore, the present study tested the possible mediating role of self-esteem and the moderating role of belief in a just world in the association between relative deprivation and loneliness of migrant children. A total of 1,261 Chinese rural-to-urban migrant children (10–15 years old, Mage = 12.34 years, SD = 1.67; 52.0% males, 48.0% females; 23.55% fourth grade students, 16.49% fifth grade students, 19.59% sixth grade students, 15.54% seventh grade students, 13.80% eighth grade students, and 10.86% ninth grade students) were recruited to complete measures of relative deprivation, self-esteem, belief in a just world, loneliness, and demographic variables. Relative deprivation was significantly and positively correlated with migrant children’s loneliness, and this connection could be mediated by self-esteem. Moreover, the first part of the indirect effect of self-esteem on this link was moderated by belief in a just world. These effects were stronger for migrant children with higher levels of belief in a just world. This study reminds us that we should pay attention to the mental health problems of migrant children and implement corresponding intervention measures, particularly for those who are lonely.